Volatile compounds contribution of Hanseniaspora guilliermondii and Hanseniaspora uvarum during red wine vinifications - Moreira, N. (2011)
This work aims to investigate the contribution of a selected non-Saccharomyces yeast species, Hanseniaspora guilliermondii, to higher alcohols, esters, fatty acids and heavy sulphur compounds composition of red wine. Red grape must vinifications of 100 l were performed and an inoculated fermentation with H. guilliermondii was compared to a spontaneous fermentation. The presence of apiculate yeasts was observed in both fermentations; however, Hanseniaspora uvarum was the only apiculate yeast isolated from the spontaneous fermentation. Apiculate yeasts dominated the fermentation until an ethanol concentration of 6% (v/v) was attained and remained in considerable high levels for an ethanol concentration of 12.5% (v/v). The grape must inoculated with H. guilliermondii led to the production of wine with higher concentrations of 1-propanol, 2-phenylethyl acetate and 3-(methylthio)propionic acid, and lower amounts of ethyl hexanoate, pentanoic acid, free fatty acids, 2-methyltetrahydrothiophen-3- one and acetic acid-3-(methylthio)propyl ester, than wine resulting from the spontaneous fermentation. The present study shows that the use of specific apiculate yeasts in grape must fermentations may lead to the production of wines with different chemical profiles, emphasising the importance of Hanseniaspora yeasts as mixed starter cultures with Saccharomyces cerevisiae, in winemaking.